Voluntary feed intake and leptin sensitivity in ad libitum fed obese ponies following a period of restricted feeding: a pilot study. Issue 4 (5th April 2012) - Van Weyenberg, S.; Buyse, J.; Kalmar, I. D.; Swennen, Q.; Janssens, G. P. J.
Summary The relation between plasma leptin and daily ad libitum roughage intake was evaluated during a 14‐day period in eight obese Shetland ponies. When the feeding strategy was changed from maintenance feeding to ad libitum feeding, feed intake increased the first day, decreased the second day and increased again during the following days to reach a constant level after 8 days. Plasma leptin concentration increased during the first 2 days, but remained constant afterwards. Although the same pattern was found in all ponies, the magnitude of the increase in leptin on day 1 and the resulting decrease in feed intake on day 2 differed between ponies. A lower anorectic effect was seen in ponies with higher initial leptin concentration, suggesting the presence of different degrees in leptin sensitivity in obese ponies. High leptin production in a attempt to compensate for the decrease in leptin sensitivity might explain large variations in plasma leptin among obese ponies with similar body condition score. Further research is necessary to clarify whether the reduced leptin sensitivity precedes obesity in equines or vice versa.